Bibliometric Analysis of Research Articles on Pain in the Elderly Published from 2000 to 2019 - Zhao, Yanqiao (J Pain Res, 2021)
BACKGROUND: Given the rapid growth of the global aging population, pain has become an unneglectable concern amongst the elderly. The quantity of scientific research outputs on pain in the elderly has increased over time, but only a small number of studies have used bibliometric methods to analyze scientific research in this field. This paper aimed to analyze scientific research on pain in the elderly published from 2000 to 2019 in a systematic manner using bibliometric methods. METHODS: Articles on pain in the elderly published from 2000 to 2019 were retrieved from the Web of Science (WoS). Abstracts were coded on the basis of predetermined items (eg, type of article, topic, type of subjects, pain characteristics), and relevant information on the first author, citation scores, and article keywords were collected. RESULTS: A total of 2105 articles were included in this study. Statistical analysis revealed that the publication of articles on pain in the elderly increased in frequency over time (P<0.001). Most of the publications were original articles. Amongst the countries identified, the United States published the largest number of papers on this topic. Pain characteristics (50.21%), pain intervention (35.68%), and pain assessment (9.69%) were the main topics of research on geriatric pain. Back pain (12.30%) appeared to be the most popular pain type described in the included papers. CONCLUSION: This work provides researchers with an in-depth understanding of pain in the elderly by evaluating relevant publications in the past two decades. Researchers in this field are warranted to explore future directions on geriatric pain such as the transition from acute pain to chronic pain and the underlying mechanisms of pain in the elderly.